2018
DOI: 10.2525/ecb.56.99
|View full text |Cite
|
Sign up to set email alerts
|

Inflorescence Developmental Stage-Specific High Temperature Effect on Petal Pigmentation in Chrysanthemum

Abstract: Flower color is one of the most important traits in ornamental plants. Poor coloration of pink flower chrysanthemum during the high temperature season is a serious problem. To determine the effect of high temperature on the pigmentation, inflorescence development was divided into five stages. Plants were exposed to both 20 and 30 during various developmental stages of inflorescence. HPLC analysis showed the main anthocyanins of pink flower chrysanthemum (cv. Pelican) were cyanidin 3-O-(6≤-O-monomalonyl-b -gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The expressions of CHS , CHI , F3H , F3′H , DFR , and ANS were shown to be affected by growth temperature using qRT-PCR in C. morifolium ‘Pelican’ 45 . They fixed the temperature at 20 °C or 30 °C all the day and used ray floret samples at the petal extension stage, early vertical stage, and petal fully open stage; the former two stages were almost consistent with our stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of CHS , CHI , F3H , F3′H , DFR , and ANS were shown to be affected by growth temperature using qRT-PCR in C. morifolium ‘Pelican’ 45 . They fixed the temperature at 20 °C or 30 °C all the day and used ray floret samples at the petal extension stage, early vertical stage, and petal fully open stage; the former two stages were almost consistent with our stages 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…The flower color was one of the most important quality aspects in ornamental plants (Puangkrit et al, 2018). Flower color depends on the accumulation of secondary compounds, including flavonoids, carotenoids, or betalains.…”
Section: Color Of Chrysanthemum Flowersmentioning
confidence: 99%
“…Studies by Nozaki et al and Huh et al reported that the pale pigmentation in pink-flowered genotypes of chrysanthemum was mainly due to a reduction of two anthocyanins (Cy 3-6’’-MMG and Cy 3-3’’,6’’-DMG) under high temperature [ 91 , 92 ]. The total anthocyanin content was found to be considerably higher at 20 °C compared with 30 °C in chrysanthemum petals [ 93 ]. Expression of anthocyanin biosynthesis-related genes, including CHS1 , CHS2 , CHI , F3H2 , C3′H , DFR1 , DFR2 , and ANS was downregulated in ray petals when the plants were exposed to 30 °C.…”
Section: External Factors Regulating Anthocyanin Biosynthesis and mentioning
confidence: 99%